2016
DOI: 10.1371/journal.pone.0147603
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Pace with Your Eating: Visual Feedback Affects Eating Rate in Humans

Abstract: Deliberately eating at a slower pace promotes satiation and eating quickly has been associated with a higher body mass index. Therefore, understanding factors that affect eating rate should be given high priority. Eating rate is affected by the physical/textural properties of a food, by motivational state, and by portion size and palatability. This study explored the prospect that eating rate is also influenced by a hitherto unexplored cognitive process that uses ongoing perceptual estimates of the volume of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Participants in the slow rate group in the study may have found it frustrating being instructed to consume their food more slowly, and that undermined enjoyment, including the enjoyment component of satisfaction. It is possible that there may be an optimal eating rate for individuals, encompassed within a window of tolerance to change; and reducing eating rate beyond that, reduces enjoyment and satisfaction from the meal (as seen here with this experimentally slow condition) which was also suggested by a previous study [53]. Exploiting the boundaries of this tolerance window may be important for the design of eating rate interventions.…”
Section: Discussionsupporting
confidence: 54%
“…Participants in the slow rate group in the study may have found it frustrating being instructed to consume their food more slowly, and that undermined enjoyment, including the enjoyment component of satisfaction. It is possible that there may be an optimal eating rate for individuals, encompassed within a window of tolerance to change; and reducing eating rate beyond that, reduces enjoyment and satisfaction from the meal (as seen here with this experimentally slow condition) which was also suggested by a previous study [53]. Exploiting the boundaries of this tolerance window may be important for the design of eating rate interventions.…”
Section: Discussionsupporting
confidence: 54%
“…The question of whether eating rate is also influenced by ongoing perceptual estimates of the volume of food remaining and by a corresponding adjustment of food intake during a meal, has also been examined [ 17 ]. Subjects were “tricked” into eating more or less than what appeared and were unaware that their portion size had been manipulated.…”
Section: Studies Concerning Healthy Individualsmentioning
confidence: 99%
“…Eating rate may also be controlled via visual feedback and is not considered a simple reflexive response to orosensory stimulation. Irrespective of food type, participants reported greater fullness at the end of the meal if they had consumed the 500 ML portion compared to participants who had eaten the 300 ML portion [ 17 ].…”
Section: Studies Concerning Healthy Individualsmentioning
confidence: 99%
“…Previous work has also shown how implicit and explicit cognitive factors can increase eating rate, such as eating while distracted (Blass et al, 2006;Bolhuis, Lakemond, de Wijk, Luning, & de Graaf, 2013), eating with others (de Castro, 1990Castro, , 1994Castro, , 1995, eating large servings (Almiron-Roig et al, 2015;Wilkinson et al, 2016) and eating highly palatable foods (Bobroff & Kissileff, 1986). Furthermore, Wilkinson et al (2016) found that the perceived volume of a food portion (rather than the volume of food consumed in reality) can influence eating rate. That is, eating rate was faster when a portion of soup seemed small (300 ml) but the portion that participants actually consumed was larger (500 ml; achieved by covertly replenishing the soup bowl via a peristaltic pump) compared to when the portion of soup in the bowl seemed larger (500 ml) but where less soup was consumed in reality (300 ml).…”
Section: Introductionmentioning
confidence: 98%
“…by verbal or computerised cues; cutlery size or vibrotactile feedback; food texture; or via oral device) have been shown to successfully reduce energy intake while increasing satiation/satiety and decreasing the risk of later energy compensation (Andrade, Kresge, Teixeira, Baptista, & Melanson, 2012;Ferriday et al, 2016;Forde, van Kuijk, Thaler, de Graaf, & Martin, 2013;Hermans et al, 2017;James, Maher, Biddle, & Broom, 2016;Ryan et al, 2018;Scisco, Muth, Dong, & Hoover, 2011). Previous work has also shown how implicit and explicit cognitive factors can increase eating rate, such as eating while distracted (Blass et al, 2006;Bolhuis, Lakemond, de Wijk, Luning, & de Graaf, 2013), eating with others (de Castro, 1990Castro, , 1994Castro, , 1995, eating large servings (Almiron-Roig et al, 2015;Wilkinson et al, 2016) and eating highly palatable foods (Bobroff & Kissileff, 1986). Furthermore, Wilkinson et al (2016) found that the perceived volume of a food portion (rather than the volume of food consumed in reality) can influence eating rate.…”
Section: Introductionmentioning
confidence: 99%